The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1177/1932296815599006
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Inspiratory Muscle Training on Changes in Fasting Hyperglycemia in the Older Adult

Abstract: Fasting hyperglycemia is often observed in the older adult population, showing that after the age of 50, fasting blood glucose levels increase by 0.06 mmol/decade. Therefore, many authors embrace the hypothesis that with aging and progressive fasting blood sugar disorders can lead to glucose intolerance and type 2 diabetes.1 Fasting hyperglycemia (100-125 mg/dl or 5.6 to 6.9 mmol/L) is defined as an intermediate state type 2 diabetes and normal levels. Older people are often faced with limitations when it come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
1
4
1
Order By: Relevance
“…Chiappa et al [27] demonstrated positive effects of IMT on blood flow in lower limbs and, thus, improvement in their function. Similar results were obtained by Silva et al [28], who performed IMT in elderly patients with insulin resistance.…”
Section: Discussionsupporting
confidence: 90%
“…Chiappa et al [27] demonstrated positive effects of IMT on blood flow in lower limbs and, thus, improvement in their function. Similar results were obtained by Silva et al [28], who performed IMT in elderly patients with insulin resistance.…”
Section: Discussionsupporting
confidence: 90%
“…133 ± 65 mg/dl). Two studies reported significant reductions in blood glucose after inspiratory muscle training in patients with insulin resistance [31] and with fasting hyperglycaemia [33]. The exercise intensity and volume in these studies were higher than in our study.…”
Section: Discussioncontrasting
confidence: 80%
“… 41 In another study by Silva et al. , 21 IMT induced a reduction in fasting glucose levels and improved the secretory capacity of pancreatic cells. These findings are at variance with the study by Ahmad et al.…”
Section: Discussionmentioning
confidence: 93%
“…17 Since there is a relationship between the cardiopulmonary function and functional capacity as well as glycemic levels in patients with T2DM, any intervention that affects the respiratory function may in turn affect the other parameters. 20 , 21 This study was therefore designed to determine the effects of IS on selected cardiopulmonary parameters, functional capacity and glycemic control in patients with T2DM and the correlation between pulmonary function and functional capacity, duration of the disease (DOD) and glycemic control.…”
Section: Introductionmentioning
confidence: 99%